(untitled) (Medical Forum Monthly, 2024)
Objective: The study aims to record the grade of resorption in maxillary teeth in patients with impacted maxillary canines. Study Design: A retrospective radiographic study Place and Duration of Study: This study was conducted at the College of Dentistry, Qassim University, Buraydah, Qassim, Saudi Arabia from June 2022 and February 2024. Methods: We collected a number of 4500 panoramic radiographs from the Radiographic Department at the dental clinics of the College of Dentistry, Qassim University. Patients ≥12 years old with good-quality panoramic radiographs were included. The root resorption severity was categorized into 4 groups (no, mild, moderate, and severe resorptions). The location of the impacted maxillary canine was divided into 5 sectors. Chi-squared test was used to identify any significant differences between genders. The Kappa test was used to assess the Intra-rater reliability for the severity of root resorption. The level of significance was set at P < 0.05. Result: A number of 19 impacted maxillary canines caused mild to severe resorption of the lateral incisors (n=17, 89.5%) and central incisors (n=2, 10.5%). The prevalence of root resorption of adjacent teeth was 17.3%. There were 12 males (66.7%) and 6 females (33.3%) affected with root resorption, with a significant difference detected (p=0.01) between the two genders. Most of the root resorption occurred with impacted canines in sectors 1 and 2 (79%). Conclusions: Impaction of maxillary canines occurred more in males than females. The root resorption occurred more frequently in male compared to female patients with highly significant differences. The most affected teeth were lateral incisors (89.5%).